Reading Comprehension Difficulties on Students’ Perception in Narrative Text at Eleventh Grade of Vocation High School - Laia, Dewi Purnamasari; Pasaribu, Arsen Nahum; Manurung, Lastri Wahyuni (Institut Agama Islam Negeri Palopo, 2024)
This research aims to identify the reading comprehension difficulties faced by eleventh-grade students and how to solve the students' reading comprehension difficulties. This research uses mixed methods with an explanatory sequential design to collect data, both quantitative and qualitative. Reading tests to collect quantitative data and interviews to collect qualitative data. Twenty students from SMKN 1 Lolomatua participated in obtaining quantitative and qualitative data. The research results showed that 76,25% of students experienced difficulty in making conclusions. Second, 44.3 % of students had difficulty determining the main idea. Third, 68,3 % of students have difficulty interpreting vocabulary. Fourth, 45 % of students found it difficult to identify references. Fifth, 52 % of students had difficulty detailing information. Then, four the strategies to solve students' difficulties in reading comprehension. They are students have to reading a lot of English books, master of the vocabularies, find synonym and antonym words, and for pronunciation students can use smartphone application.